Group‐based behavioral skills training to promote effective instruction delivery for children with autism spectrum disorder. (25th January 2021) - LaBrot, Zachary C.; Kupzyk, Sara; Pasqua, Jamie L.; Fox Wagner, Shelby
Abstract: Children with autism spectrum disorder are at increased risk for noncompliance with parent instructions and subsequent disruptive behaviors. Effective instruction delivery is an antecedent‐based strategy designed to prevent noncompliance with parent instructions and given its components, may be especially useful for promoting compliance in children with autism. However, long wait times for behavioral parent training could lead to increased severity of behavioral difficulties prior to receiving services. The purpose of this study was to examine the effectiveness of group‐based behavioral skills training for increasing effective instruction delivery with their children diagnosed with autism spectrum disorder. Results indicated improved use of effective instruction delivery with concomitant improvements in children's response to parent instructions. Results, implications, and future directions are discussed.